Sclerostin and Its Association with Physical Activity, Age, Gender, Body Composition, and Bone Mineral Content in Healthy Adults - Amrein, Karin; Amrein, Steven; Drexler, Camilla; Dimai, Hans Peter; Dobnig, Harald; Pfeifer, Klaus; Tomaschitz, Andreas; Pieber, Thomas R.; Fahrleitner-Pammer, Astrid (The journal of clinical endocrinology and metabolism, 2012)
Context:Sclerostin is produced by osteocytes and inhibits bone formation through the Wnt/β-catenin-signaling pathway. Only limited data are available on circulating sclerostin levels in healthy subjects.Objective:We aimed to evaluate the correlation between sclerostin and physical activity, anthropometric, and biochemical variables.Design, Setting, and Participants:We conducted a cross-sectional observational study in 161 healthy adult men and premenopausal women aged 19 to 64 yr (mean age, 44 ± 10).Intervention(s):There were no interventions.Main Outcome Measure(s):Serum sclerostin levels were associated with body composition, bone mineral density, physical activity, and various biochemical parameters.Results:A positive correlation between age and sclerostin in both men (r = 0.37; P < 0.001) and premenopausal women (r = 0.66; P < 0.001) was found. Men had significantly higher sclerostin levels than women (49.8 ± 17.6 vs. 37.2 ± 15.2 pmol/liter; P < 0.001). However, after adjustment for age, bone mineral content (BMC), physical activity, body mass index (BMI), and renal function, sclerostin levels did not differ (P = 0.543). Partial correlation analysis adjusted for age, gender, and kidney function revealed a significant positive correlation between sclerostin levels and BMC, bone mineral density, BMI, and android/gynoid fat and a significant negative correlation with serum osteocalcin and calcium. The most physically active quartile had significantly lower sclerostin levels compared to the least active quartile in a univariate analysis.Conclusions:In healthy adults, sclerostin serum levels correlate positively with age, BMI, and BMC and negatively with osteocalcin and calcium. Further studies in larger populations are needed to confirm our findings and to better understand their clinical implications.